Multicultural Neurolinguistics: A Neuroscientific Perceptive of Cross-Cultural Differences in Translation - Huang, Wei; Agbanyo, George Kwame (Frontiers in Psychology, 2022)
Psycholinguistics and neurolinguistics have been seldom used in investigating the cultural component of language. In this study, we suggest a scientific methodology to study neurocognitive mechanisms induced by the interaction between multi-linguistics and cross-culture differences, especially during translation between a source language (SL) and a target language (TL). Using a contest of tonal languages (Chinese) and atonal language (English) multilingual exchange, we opine that translation theories as numerous and efficacious as they are, lack the competence to bring absolute clarity into the complex cross-cultural dimension of languages when it comes to accuracy in translation. Echoing this, this study attempts to apply neuroscience in blending cross-cultural diversity and neurolinguistics as a one-in-all translation approach to “multicultural neurolinguistics” between an SL and a given TL. The linguistic examination of this study proves that “multicultural neurolinguistics” will provide a unique framework for all translation barriers, and establish a cross-cultural and multilingual network depending on the particular circumstance. This research contributes to the linguistic literature by bringing a “multicultural neurolinguistics” resolution to the cultural diversity question in translation.